Computing Strain Rate Effects on Concrete Compressive Strength by Smoothed Particle Hydrodynamics - Saavedra-Flores, E; Droguett-Aguila, C; Yanez-Cart, S (Springer Science and Business Media Deutschland GmbH, 2024)
In this paper, the influence of strain rate on the compressive response of concrete specimens is investigated by means of Smoothed Particle Hydrodynamics simulations. The material response is described by the RHT model, which combines three independent strength surfaces with a non-linear equation of state for shock waves. Concrete cubes made of normal strength of 35 MPa are subjected to uniaxial compression loads at different strain rates. In particular, high strain rate effects are assessed on the shape of load–displacement curves, maximum compressive strength, and damage pattern. The present work provides further insight into the complex mechanisms of compressive failure behaviour of concrete materials under high strain rates, with potential applications to the future design of more resilient structures when subjected to earthquake and blast loading cases. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.